2016
DOI: 10.13005/bbra/2044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Massage Therapy on Physiologic Responses in Patients with Congestive Heart Failure

Abstract: Congestive heart failure (CHF) is the inability of the myocardium to pump enough blood to meet the body's metabolic demands. This study was conducted to assess the effects of effect of massage therapy on physiologic responses in patients with congestive heart failure. This study was a quasi-experimental, done with the permission of Jahrom University of Medical Sciences that conducted on two CCU wards of hospitals of Jahrom. Fifty participants were recruited to participate in this study within 24 hours after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…11,13,16 Additionally, a few reports indicate that CM has also promising effects on the relief of fatigue and sleep problems. 11,13,16 A quasi-experimental study has highlighted that performing classical back massage application for 20 minutes up to 3 days in patients hospitalized with HF reduced fatigue severity. 16 A recent quasi-experiment study investigating the effects of classical back massage on sleep quality in patients with congestive HF also indicated that sleep quality significantly improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,16 Additionally, a few reports indicate that CM has also promising effects on the relief of fatigue and sleep problems. 11,13,16 A quasi-experimental study has highlighted that performing classical back massage application for 20 minutes up to 3 days in patients hospitalized with HF reduced fatigue severity. 16 A recent quasi-experiment study investigating the effects of classical back massage on sleep quality in patients with congestive HF also indicated that sleep quality significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacologic approaches are usually utilized simultaneously with the current pharmacologic approaches to reduce drug side effects, provide physiological and psychosocial well-being, and improve the QoL 11,12. The National Center for Complementary and Integrative Health classifies nonpharmacologic approaches into 5 categories: (1) alternative medical systems, (2) biologically based therapies, (3) manipulative and body-based methods, (4) energy therapies, and (5) mind-body interventions 10,12.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, below one-third of participants took it as an alternative and complementary therapy. However, some studies mentioned that massage, particularly in the back, was found to significantly reduce systolic BP, especially in the male patients, increase pulmonary function, stimulate circulation (Chen et al, 2013b), improve anxiety (Ramezanli et al, 2016), and to stabilize vital signs (Jamali et al, 2016). The mean number of CV medications used in this study was slightly higher than the Chen et al (2009) study, with antiplatelets appeared as the most used CV medication (78.4%).…”
Section: Discussionmentioning
confidence: 50%
“…Massage played an important role in sleep quality, accounted for 4.3% of the variance in the global PSQI score. Some previous studies stated that massage as a complementary therapy might help patients to stabilize their vitals signs (Jamali et al, 2016), reduce anxiety and increase comfort (Chen et al, 2013b), and promote sleep (Evangelista et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A large and growing body of research justifies the use of massage therapy for pain management in the acute care setting. Massage therapy was effective in blood pressure, heart rate, respiration rate, and O 2 saturation in patients with congestive heart failure (Jamali, Ramezanli, Jahromi, Zare, & Poorgholami, 2016). Using tactile massage may give nurses a tool in their work, may change their caregiving practice, and may increase their own and their patients’ well-being in a stressful environment as the short-term emergency ward (Airosa, Falkenberg, Öhlén, & Arman, 2016).…”
Section: Touch In Nursingmentioning
confidence: 99%